2010
DOI: 10.1783/147118910791749380
|View full text |Cite
|
Sign up to set email alerts
|

The context of unintended pregnancy among married women in the USA

Abstract: Background and methodology Unintended pregnancy is a concern in the USA due to its association with adverse physical, mental, social and economic outcomes. Few studies have examined this issue among married women from a social and contextual perspective. This study targeted married women to examine factors associated with unintended pregnancy using the ecological model of health promotion that focuses attention on both individual and social environmental factors. Data from the National Survey of Family Growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
1
20
4
Order By: Relevance
“…Nevertheless, unlike other studies [16][17][18], it was not a determining factor in quality of life. Additionally, contrary to the results of other studies [19,20], the results of the present study demonstrated that economic status; number of pregnancies, and age…”
Section: Discussioncontrasting
confidence: 99%
“…Nevertheless, unlike other studies [16][17][18], it was not a determining factor in quality of life. Additionally, contrary to the results of other studies [19,20], the results of the present study demonstrated that economic status; number of pregnancies, and age…”
Section: Discussioncontrasting
confidence: 99%
“…Another issue with this study is response bias; participants may not want to indicate their pregnancy was unintended, as they may equate this with an unwanted pregnancy. We did not collect information on parity, which may have affected pregnancy intention, as higher parity has been associated with increased rates of unintended pregnancy 27 . Finally, the pregnancy intention instrument used in this study has not been validated within the Australian population and the demographic characteristics on which the instrument was validated vary from those of the population of Australian women in this study, which may have an impact on interpretation of the questions and, subsequently, women's answers to these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Although information about demographics, couples’ behaviors, and risk-taking strategies related to abortion have been documented, less is known about individual and community-level factors associated with men in this population (Koran & Mawn, 2010; Luker, 1976). A survey related to this topic conducted with 283 men from an urban community health center population found acknowledgment that IPV perpetration was common and associated with sexual risk-taking, minimal condom use, and having fathered three or more children; however, specific attention to pregnancy intention was not included in the analysis (Raj et al, 2006).…”
Section: The Relationship Between Unintended Pregnancy and Violencementioning
confidence: 99%